Positive electrode material, preparation method thereof and battery
The carbon-coated lithium iron phosphate and iron phosphide were generated through sand milling and heat treatment, which solved the problem of insufficient energy density of lithium iron phosphate positive electrode material, achieved the balance of energy density and electrochemical performance, and significantly improved the kinetic performance and gram capacity.
Patent Information
- Application Number
- CN202411245025.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
AI Technical Summary
The working voltage and theoretical capacity of lithium iron phosphate cathode material are low, resulting in insufficient energy density. The existing modification methods are difficult to take into account both electrochemical properties while increasing the compaction density.
By dispersing iron phosphate, lithium source and modifier in aqueous solution, sanding and heat treatment, carbon-coated lithium iron phosphate and carbon-coated iron phosphide are generated, and the median particle size and heat treatment of the mixed sand grinding solution are controlled. According to conditions, a positive electrode material with a strong interfacial coupling effect is formed.
The kinetic performance of lithium iron phosphate is significantly improved, the capacity and rate performance are improved, the resistivity is reduced, the energy density and electrochemical performance is achieved, the use of conductive agents is reduced, and the volume and mass energy density is improved.
Smart Images

Figure CN119133395A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode material and a preparation method thereof, and a battery. Background Art
[0002] Lithium iron phosphate has become a relatively mature cathode material due to its advantages of being green, economical, and efficient. It is widely used in new energy vehicle power batteries and energy storage power stations. However, due to the relatively low working voltage and theoretical gram capacity of lithium iron phosphate, it is impossible to achieve a very high energy density, which limits the further application of this material. Since the voltage window and theoretical gram capacity of lithium iron phosphate are both fixed, in order to meet the requirements of power batteries, improving its compaction density while ensuring electrochemical performance is the key to further improving its energy density. At present, the main modification methods for obtaining high-density lithium iron phosphate cathode materials include particle size grading, element doping, surface carbon coating, and material composite. However, these methods will lead to a decrease in electrochemical performance while increasing the compaction density, making it difficult to achieve a balance between energy density and electrochemical performance. Summary of the invention
[0003] In view of this, the embodiments of the present application provide a positive electrode material, a preparation method thereof, and a battery to solve at least one problem existing in the background technology.
[0004] In a first aspect, an embodiment of the present application provides a method for preparing a positive electrode material, the method comprising the following steps:
[0005] S1: dispersing iron phosphate, a lithium source and a modifier in an aqueous solution to obtain a mixed solution; the iron phosphate comprises at least a first type of iron phosphate and a second type of iron phosphate, the iron-phosphorus ratio of the first type of iron phosphate is 95% to 96.5%, and the iron-phosphorus ratio of the second type of iron phosphate is 96.5% to 98%; the modifier comprises a carbon source;
[0006] S2: sand-milling the mixed solution to obtain a mixed sand-milled solution, wherein the median particle size Dv50 of the mixed sand-milled solution is 0.31 μm to 0.4 μm;
[0007] S3: drying the mixed sand-milled solution to obtain a mixed powder;
[0008] S4: The mixed powder is heat-treated and then crushed to obtain the positive electrode material including carbon-coated lithium iron phosphate and carbon-coated iron phosphide.
[0009] In combination with the first aspect of the present application, in an optional implementation, the mass ratio of the first type of iron phosphate to the second type of iron phosphate is (1:9) to (4:1).
[0010] In combination with the first aspect of the present application, in an optional embodiment, the modifier also includes a dopant, and the dopant includes at least one of a Mg compound, a Ti compound, a V compound, a Zr compound, a Mn compound, a Nb compound, a Mo compound, and a B compound.
[0011] In combination with the first aspect of the present application, in an optional embodiment, the lithium source includes at least one of lithium carbonate, lithium nitrate, lithium hydroxide, and lithium acetate; and / or the carbon source includes at least one of sucrose, glucose, starch, polyethylene glycol, carbon black, carbon fiber tubes, graphite, and graphene.
[0012] In combination with the first aspect of the present application, in an optional implementation, the heat treatment includes sequentially performing a first sintering and a second sintering on the mixed powder.
[0013] In conjunction with the first aspect of the present application, in an optional embodiment, the heat treatment satisfies at least one of the following features (1) to (6):
[0014] (1) The heating rate of the first sintering is 1°C / min to 10°C / min;
[0015] (2) The sintering temperature of the first sintering is 200° C. to 350° C.;
[0016] (3) The sintering time of the first sintering is 1 h to 5 h;
[0017] (4) The heating rate of the second sintering is 1°C / min to 10°C / min;
[0018] (5) The sintering temperature of the second sintering is 750° C. to 840° C.;
[0019] (6) The sintering time of the second sintering is 6 hours to 15 hours.
[0020] In a second aspect, an embodiment of the present application provides a positive electrode material, including:
[0021] Carbon-coated lithium iron phosphate;
[0022] Carbon-coated iron phosphide, the carbon-coated iron phosphide is distributed between the particles of the carbon-coated lithium iron phosphate; the content of the carbon-coated lithium iron phosphate is 98wt% to 99.99wt%, and the content of the carbon-coated iron phosphide is 0.01wt% to 2wt%.
[0023] In conjunction with the second aspect of the present application, in an optional embodiment, the positive electrode material satisfies at least one of the following features (1) to (5):
[0024] (1) The median particle size Dv50 of the positive electrode material is 0.7 μm to 2.5 μm;
[0025] (2) The carbon content in the positive electrode material is 1.0wt% to 1.6wt%;
[0026] (3) The resistivity of the positive electrode material is 1Ω·cm to 20Ω·cm;
[0027] (4) The compaction density of the positive electrode material is 2.5 g / cm 3 ~2.8g / cm 3 ;
[0028] (5) The particle size of the iron phosphide in the carbon-coated iron phosphide is 0.1 μm to 3 μm.
[0029] In conjunction with the second aspect of the present application, in an optional implementation, the positive electrode material further includes:
[0030] The dopant includes at least one of a Mg compound, a Ti compound, a V compound, a Zr compound, a Mn compound, a Nb compound, a Mo compound, and a B compound.
[0031] In a third aspect, an embodiment of the present application provides a battery, comprising a positive electrode plate, wherein the positive electrode plate comprises a positive electrode material prepared by the preparation method as described in any one of the first aspect, or comprises a positive electrode material as described in any one of the second aspect.
[0032] Compared with the prior art, the embodiments of the present application have the following beneficial effects:
[0033] The positive electrode material, preparation method and battery provided in the embodiments of the present application are obtained by sand milling and heat treating a mixed solution containing a first type of iron phosphate, a second type of iron phosphate, a lithium source and a carbon source to obtain the positive electrode material. Since the first type of iron phosphate in the iron phosphate has a relatively low iron-phosphorus ratio, the median particle size Dv50 of the mixed sand milled solution is controlled within a relatively low range of 0.31 μm to 0.4 μm, so that the first type of iron phosphate generates iron phosphide during the heat treatment after sand milling, and the obtained positive electrode material includes carbon-coated lithium iron phosphate and carbon-coated iron phosphide. On the one hand, the formation of iron phosphide can prevent the fusion of small lithium iron phosphate particles to form overly large primary particles during the sintering process, thereby avoiding affecting the gram capacity, low temperature performance and rate performance. On the other hand, the combination of ferromagnetic iron phosphide and antiferromagnetic lithium iron phosphate can produce a strong interface coupling effect between the two substances. This effect can reduce the electron transfer resistance in the electrode, significantly improve the kinetic performance of large lithium iron phosphate particles, and allow large particles to exert a higher gram capacity, thereby significantly improving the gram capacity, rate performance and cycle performance of lithium iron phosphate materials, thereby achieving a balance between the energy density and electrochemical performance of the positive electrode material. In addition, iron phosphide has excellent conductivity. Due to the presence of iron phosphide, the resistivity of the positive electrode material can be significantly reduced. When the positive electrode material is used in the positive electrode sheet active material, the conductive agent can be reduced or even not used, thereby further increasing the content and compaction density of the positive electrode material in the positive electrode sheet active material, thereby achieving the effect of simultaneously increasing the volume energy density and mass energy density.
[0034] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0036] Figure 1 A schematic diagram of a process for preparing a positive electrode material provided in an embodiment of the present application;
[0037] Figure 2 XRD diagrams of the positive electrode materials prepared in Example 2 and Comparative Example 1;
[0038] Figure 3 for Figure 2 A local enlarged view of point A;
[0039] Figure 4 This is a scanning electron microscope image of the positive electrode material prepared in Example 2;
[0040] Figure 5 For the corresponding Figure 4 Energy spectrum scan of Fe element in the middle area;
[0041] Figure 6 For the corresponding Figure 4 Energy spectrum of O element in the middle area;
[0042] Figure 7 For the corresponding Figure 4 Energy spectrum of P element in the middle area;
[0043] Figure 8 The discharge curves of batteries made of the positive electrode materials obtained in Example 2 and Comparative Example 1 at different rates;
[0044] Fig. 9 The cycle performance test curves of batteries made of the positive electrode materials obtained in Example 1 and Comparative Example 1 at 45°C. DETAILED DESCRIPTION
[0045] In order to make the technical scheme and beneficial effects of the present invention more obvious and easy to understand, the following is described in detail by combining the accompanying drawings and listing specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually based on conventional experimental conditions. The reagents and raw materials used in the present invention are commercially available unless otherwise specified.
[0046] In the following description, a large number of specific details are given to provide a more thorough understanding of the present application. However, it is obvious to those skilled in the art that the present application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application, some technical features known in the art are not described; that is, all features of the actual embodiments are not described here, and well-known functions and steps are not described in detail.
[0047] The purpose of the terms used herein is only to describe specific embodiments and is not intended to be limiting of the present application. When used herein, the singular forms "one", "an" and "said / the" are also intended to include plural forms, unless the context clearly indicates otherwise. It should also be understood that the terms "consisting of" and / or "comprising", when used in this specification, determine the presence of the features, integers, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts and / or groups. When used herein, the term "and / or" includes any and all combinations of the relevant listed items.
[0048] In order to thoroughly understand the present application, detailed steps and detailed structures will be presented in the following description to illustrate the technical solution of the present application. The preferred embodiments of the present application are described in detail below, but in addition to these detailed descriptions, the present application may also have other implementation methods.
[0049] Unless otherwise defined, technical and scientific terms used in this application have the same meanings as those in the technical field to which this application belongs.
[0050] If no specific techniques or conditions are specified in the following examples, the conventional techniques or conditions described in the literature in the art, or the conditions recommended by the product instructions and the manufacturer are generally used. The numerical ranges in the following examples all include the endpoint values.
[0051] At present, one process route for synthesizing lithium iron phosphate is the phosphate railway route, that is, using iron phosphate and lithium source as raw materials, and preparing lithium iron phosphate through mixing, sand milling and sintering. When using the iron phosphate process route to prepare high-density lithium iron phosphate, the sand milling particle size of the precursor in the sand milling process and the sintering conditions are mainly adjusted to achieve the size particle grading of lithium iron phosphate, thereby improving the compaction density and improving the energy density. However, due to the presence of large particles, the rate performance of the positive electrode material is poor. In the related art, the rate performance of high-density lithium iron phosphate is improved by reducing the content of large particles or carbon coating technology. Although reducing the content of large particles can improve the rate performance to a certain extent, it will also affect the compaction density, thereby affecting the battery performance. Moreover, the higher the carbon content of the carbon coating, the higher the residual carbon content. The residual carbon will be in direct contact with the electrolyte, resulting in an increase in side reactions, further affecting the battery's cycle performance.
[0052] Based on this, the present application embodiment provides a method for preparing a positive electrode material. Figure 1 The method for preparing the modified positive electrode material provided in the embodiment of the present application comprises the following steps:
[0053] S1: dispersing iron phosphate, a lithium source and a modifier in an aqueous solution to obtain a mixed solution; the iron phosphate comprises at least a first type of iron phosphate and a second type of iron phosphate, the iron-to-phosphorus ratio of the first type of iron phosphate is 95% to 96.5%, and the iron-to-phosphorus ratio of the second type of iron phosphate is 96.5% to 98%; the modifier comprises a carbon source;
[0054] S2: sand-milling the mixed solution to obtain a mixed sand-milled solution, wherein the median particle size Dv50 of the mixed sand-milled solution is 0.31 μm to 0.4 μm;
[0055] S3: drying the mixed sand-milled solution to obtain a mixed powder;
[0056] S4: The mixed powder is heat-treated and then crushed to obtain a positive electrode material including carbon-coated lithium iron phosphate and carbon-coated iron phosphide.
[0057] In an embodiment of the present application, a positive electrode material is obtained by sand milling and heat treating a mixed solution comprising a first type of iron phosphate, a second type of iron phosphate, a lithium source and a carbon source. Since the first type of iron phosphate in the iron phosphate has a relatively low iron-phosphorus ratio, the median particle size Dv50 of the mixed sand milled solution is controlled within a relatively low range of 0.31 μm to 0.4 μm, so that the first type of iron phosphate generates iron phosphide during the heat treatment process after sand milling, and the obtained positive electrode material includes carbon-coated lithium iron phosphate and carbon-coated iron phosphide. On the one hand, the formation of iron phosphide can prevent the fusion of small lithium iron phosphate particles to form overly large primary particles during the sintering process, thereby avoiding affecting the gram capacity, low temperature performance and rate performance. On the other hand, the combination of ferromagnetic iron phosphide and antiferromagnetic lithium iron phosphate can produce a strong interface coupling effect between the two substances. This effect can reduce the electron transfer resistance in the electrode, significantly improve the kinetic performance of large lithium iron phosphate particles, and allow large particles to exert a higher gram capacity, thereby significantly improving the gram capacity, rate performance and cycle performance of lithium iron phosphate materials, thereby achieving a balance between the energy density and electrochemical performance of the positive electrode material. In addition, iron phosphide has excellent conductivity. Due to the presence of iron phosphide, the resistivity of the positive electrode material can be significantly reduced. When the positive electrode material is used in the positive electrode sheet active material, the conductive agent can be reduced or even not used, thereby further increasing the content and compaction density of the positive electrode material in the positive electrode sheet active material, thereby achieving the effect of simultaneously increasing the volume energy density and mass energy density.
[0058] In an embodiment of the present application, the particle size of the mixed sand-milling solution is controlled within a relatively low range by sand-milling, for example, it may be 0.31 μm, 0.33 μm, 0.35 μm, 0.37 μm, 0.38 μm, 0.4 μm or any value between any two of the above numerical ranges. This can increase the specific surface area of the first type of iron phosphate in the mixed sand-milling solution, so that the first type of iron phosphate is better hydrolyzed during the sand-milling process, and the hydrolysis product of the first type of iron phosphate will form iron phosphide during the heat treatment process.
[0059] In the embodiment of the present application, iron phosphide and lithium iron phosphate are formed during the heat treatment process, part of the iron phosphide is distributed between the small lithium iron phosphate particles, and part of the iron phosphide is distributed in the large particles of lithium iron phosphate that are not completely fused, which can prevent the particles from merging to form overly large primary particles, thereby significantly improving the kinetics of the unfused lithium iron phosphate particles, exerting a higher gram capacity, and thus achieving a balance between the energy density and rate performance of the positive electrode material. That is, in the present application, there is no coating relationship between the iron phosphide and the lithium iron phosphate, and the carbon source forms a coating layer on the surface of the iron phosphide and the lithium iron phosphate, respectively, so that the carbon-coated iron phosphide is distributed between the carbon-coated lithium iron phosphate particles, so that the compaction density and electrochemical performance of the positive electrode material can be improved.
[0060] For example, the iron-phosphorus ratio of the first type of iron phosphate in the embodiment of the present application can be 95%, 95.1%, 95.3%, 95.6%, 96%, 96.2%, 96.4%, 96.5% or any value between any two of the above numerical ranges. The iron-phosphorus ratio of the second type of iron phosphate can be 96.5%, 96.8%, 97%, 97.2%, 97.5%, 97.8%, 98% or any value between any two of the above numerical ranges.
[0061] In some embodiments, the mass ratio of the first type of iron phosphate to the second type of iron phosphate can be (1:9) to (4:1), for example, (1:9), (1:7), (1:5), (1:3), (1:1), (2:1), (3:1), (4:1) or any value between any two of the above ranges. By controlling the mass ratio of the first type of iron phosphate to the second type of iron phosphate within the above range, the carbon-coated iron phosphide and the carbon-coated lithium iron phosphate in the prepared positive electrode material can have appropriate proportions, thereby further improving the performance of the positive electrode material.
[0062] It can be understood that the carbon-coated iron phosphide in the positive electrode material cannot contribute to the capacity of the positive electrode material. Therefore, too high a content of carbon-coated iron phosphide will result in a lower gram capacity of the positive electrode material. Therefore, in some specific embodiments, by controlling the mass ratio of the first type of iron phosphate to the second type of iron phosphate, the content of carbon-coated lithium iron phosphate in the positive electrode material can be controlled within the range of 98wt% to 99.99wt%, and the content of carbon-coated iron phosphide can be controlled within the range of 0.01wt% to 2wt%. In this way, the compaction density and rate performance of the positive electrode material can be taken into account, and the electrochemical performance can be guaranteed while ensuring the gram capacity.
[0063] It can be understood that in addition to the first type of iron phosphate and the second type of iron phosphate, the iron phosphate may also include other types of iron phosphate, wherein the mass fraction of the first type of iron phosphate in the total iron phosphate may be 10% to 80%, and the mass fraction of the second type of iron phosphate in the total iron phosphate may be 20% to 90%. In this way, the carbon-coated iron phosphide and the carbon-coated lithium iron phosphate in the prepared positive electrode material can have appropriate proportions, thereby further improving the performance of the positive electrode material.
[0064] In some embodiments, the modifier may further include a dopant, such as at least one of a Mg compound, a Ti compound, a V compound, a Zr compound, a Mn compound, a Nb compound, a Mo compound, and a B compound.
[0065] Since the ionic conductivity and electronic conductivity of the lithium iron phosphate material itself are relatively poor, in the embodiments of the present application, on the basis of improving the ionic conductivity and electrical conductivity of the positive electrode material by carbon coating, doping the positive electrode material with dopants can further improve the ionic conductivity and electronic conductivity of the positive electrode material, thereby better improving the electrochemical properties of the positive electrode material.
[0066] There is no particular limitation on the doping amount of the dopant in the embodiments of the present application, and those skilled in the art can select it according to the target performance of the positive electrode material.
[0067] There is no particular restriction on the types of lithium source and carbon source in the above step S1, and they can be selected according to actual needs.
[0068] “Lithium source” refers to a compound for providing lithium. For example, the lithium source may include at least one of lithium carbonate, lithium nitrate, lithium hydroxide, and lithium acetate.
[0069] "Carbon source" refers to a compound for providing carbon. Exemplarily, the carbon source may include at least one of sucrose, glucose, starch, polyethylene glycol, carbon black, carbon fiber tube, graphite, and graphene.
[0070] In some embodiments, the drying of the mixed sand-milling solution in the above step S3 may be performed by spray drying to obtain a uniformly mixed powder.
[0071] In some embodiments, the heat treatment in the above step S4 includes: performing a first sintering and a second sintering on the mixed powder in sequence. Usually, the temperature of the first sintering is lower than the temperature of the second sintering. During the first sintering process, the carbon source can be fully decomposed to prepare for the formation of carbon-coated lithium iron phosphate and carbon-coated iron phosphide. During the second sintering process, the synthesis and growth of lithium iron phosphate, the formation of iron phosphide, and the coating of the carbon source on the surface of lithium iron phosphate and iron phosphide are mainly carried out. Through the two sintering stages, the carbon source can be more evenly and fully coated on the surface of lithium iron phosphate and iron phosphide, which is conducive to the formation of a positive electrode material with a suitable particle size and better electrochemical performance.
[0072] When the temperature of the first sintering is low, the carbon source cannot be fully decomposed, which is not conducive to the full coating of lithium iron phosphate and iron phosphide by the carbon source. When the temperature of the first sintering is high, lithium iron phosphate and iron phosphide may be formed in large quantities before the carbon source is fully decomposed, so that lithium iron phosphate and iron phosphide cannot be well coated by the carbon source. Therefore, in some specific embodiments, the sintering temperature of the first sintering can be 200°C to 350°C, for example, 200°C, 220°C, 250°C, 270°C, 300°C, 330°C, 350°C or any value between any two of the above numerical ranges. In this way, the carbon source can be fully decomposed, and the sintering raw materials can be fully preheated to provide better conditions for the second sintering.
[0073] In some specific embodiments, the sintering time of the first sintering can be 1 hour to 5 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours or any value between any two of the above numerical ranges. Controlling the sintering time of the first sintering within the above range can make the carbon source more fully decomposed and preheat the sintering raw materials more uniformly, so that the quality of the final positive electrode material is better.
[0074] In some specific embodiments, the heating rate of the first sintering can be 1°C / min to 10°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 5°C / min, 7°C / min, 8°C / min, 10°C / min or any value between any two of the above ranges. Controlling the heating rate within the above range can make the material heated more evenly, that is, the temperature distribution inside the material is more even.
[0075] It can be understood that the sintering temperature, sintering time and heating rate range of the first sintering mentioned above can be arbitrarily combined, for example, any two or all three can be combined, so as to achieve a better sintering effect and further improve the performance of the prepared positive electrode material.
[0076] When the temperature of the second sintering is low, it is not conducive to the formation of lithium iron phosphate and iron phosphide. When the temperature of the second sintering is high, the synthesis and growth rate of lithium iron phosphate and iron phosphide is fast, which is not convenient for controlling the particle size of the positive electrode material finally formed. Therefore, in some specific embodiments, the sintering temperature of the second sintering can be 750°C to 840°C, for example, it can be 750°C, 770°C, 790°C, 800°C, 810°C, 830°C, 840°C or any value between any two of the above numerical ranges. In this way, the controllability of the preparation process can be better, and the capacity performance and electrochemical performance of the prepared positive electrode material are better.
[0077] In some specific embodiments, the sintering time of the second sintering can be 6h to 15h, for example, 6h, 8h, 10h, 12h, 13h, 15h or any value between any two of the above ranges. Controlling the sintering time of the second sintering within the above range can make the formation reaction of lithium iron phosphate and iron phosphide more complete, and make the carbon source more fully coated with lithium iron phosphate and iron phosphide, so that the performance of the final cathode material is better.
[0078] In some specific embodiments, the heating rate of the second sintering can be 1°C / min to 10°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 5°C / min, 7°C / min, 8°C / min, 10°C / min or any value between any two of the above ranges. Controlling the heating rate within the above range can make the material heated more evenly, that is, the temperature distribution inside the material is more even.
[0079] It can be understood that the sintering temperature, sintering time and heating rate range of the second sintering mentioned above can be arbitrarily combined, for example, any two or all three can be combined, so as to achieve a better sintering effect and make the performance of the prepared positive electrode material better.
[0080] Based on this, an embodiment of the present application also provides a positive electrode material, including: carbon-coated lithium iron phosphate; carbon-coated iron phosphide, the carbon-coated iron phosphide is distributed between the particles of the carbon-coated lithium iron phosphate; the content of the carbon-coated lithium iron phosphate is 98wt% to 99.99wt%, and the content of the carbon-coated iron phosphide is 0.01wt% to 2wt%.
[0081] In the embodiment of the present application, the combination of ferromagnetic iron phosphide and antiferromagnetic lithium iron phosphate can produce a strong interface coupling effect between the two substances, which can reduce the electron transfer resistance in the electrode, significantly improve the kinetic performance of large lithium iron phosphate particles, and allow large particles to exert a higher gram capacity, thereby significantly improving the gram capacity, rate performance and cycle performance of lithium iron phosphate materials, thereby achieving a balance between the energy density and electrochemical performance of the positive electrode material. In addition, iron phosphide has excellent electrical conductivity. Due to the presence of iron phosphide, the resistivity of the positive electrode material can be significantly reduced. When the positive electrode material is used in the positive active material, the conductive agent can be reduced or even not used, thereby further improving the content and compaction density of the positive electrode material in the positive active material, thereby achieving the effect of simultaneously improving the volume energy density and mass energy density.
[0082] In the actual preparation process of the positive electrode material in the embodiment of the present application, the positive electrode material can be obtained by sand milling and heat treating a mixed solution containing the first type of iron phosphate, the second type of iron phosphate, a lithium source and a carbon source. Since the first type of iron phosphate in the iron phosphate has a relatively low iron-phosphorus ratio, the median particle size Dv50 of the mixed sand milling solution is controlled in a relatively low range of 0.31 μm to 0.4 μm, so that the first type of iron phosphate generates iron phosphide during the heat treatment process after sand milling, and the obtained positive electrode material includes carbon-coated lithium iron phosphate and carbon-coated iron phosphide. The generation of iron phosphide can prevent the formation of excessively large primary particles from the fusion of small particles of lithium iron phosphate during the sintering process, thereby avoiding affecting the gram capacity, low temperature performance and rate performance, so as to take into account the gram capacity and electrochemical performance of the positive electrode material.
[0083] In some embodiments, the median particle size Dv50 of the positive electrode material may be 0.7 μm to 2.5 μm. The median particle size of the positive electrode material within the above range may improve the performance of the positive electrode sheet prepared using the positive electrode material.
[0084] The carbon content in the positive electrode material is directly related to the carbon coating in the carbon-coated lithium iron phosphate and the carbon-coated iron phosphide. A thin carbon coating has a limited effect on the improvement of the electrochemical performance of the positive electrode material. A thick carbon coating easily leads to a high amount of residual carbon in the positive electrode material. The residual carbon will directly contact the electrolyte, resulting in an increase in side reactions, thereby affecting the electrochemical performance of the positive electrode material. Therefore, in some embodiments, the carbon content in the positive electrode material can be 1.0wt% to 1.6wt%.
[0085] In the embodiment of the present application, since the positive electrode material includes carbon-coated iron phosphide, the iron phosphide has excellent conductivity at room temperature (conductivity is about 1.5S / cm), and the resistivity of the positive electrode material can be adjusted by controlling the content of carbon-coated iron phosphide in the positive electrode material. In some embodiments, the resistivity of the positive electrode material can be 1Ω·cm to 20Ω·cm. Controlling the resistivity of the positive electrode material within the above range can further improve the conductivity of the positive electrode material. When the positive electrode material is used in the positive electrode sheet active material, the conductive agent can be further reduced or even eliminated, thereby further improving the content and compaction density of the positive electrode material in the positive electrode sheet active material, thereby achieving the effect of further improving the volume energy density and mass energy density.
[0086] In some embodiments, the compaction density of the positive electrode material can be 2.5 g / cm 3 ~2.8g / cm 3 Controlling the compaction density of the positive electrode material within the above range can further improve the gram capacity and rate performance of the positive electrode material.
[0087] In the embodiments of the present application, the size of the carbon-coated iron phosphide is related to the size of the positive electrode material, the compaction density of the positive electrode material, and the electrochemical performance. In some embodiments, the particle size of the iron phosphide in the carbon-coated iron phosphide can be 0.1 μm to 3 μm. Controlling the particle size of the iron phosphide within the above range can make the performance of the positive electrode material better.
[0088] In some embodiments, the positive electrode material may further include: a dopant, the dopant including at least one of a Mg compound, a Ti compound, a V compound, a Zr compound, a Mn compound, a Nb compound, a Mo compound, and a B compound.
[0089] Since the ionic conductivity and electronic conductivity of the lithium iron phosphate material itself are relatively poor, in the embodiments of the present application, on the basis of improving the ionic conductivity and electrical conductivity of the positive electrode material by carbon coating, doping the positive electrode material with dopants can further improve the ionic conductivity and electronic conductivity of the positive electrode material, thereby better improving the electrochemical properties of the positive electrode material.
[0090] In some embodiments, the positive electrode material can be prepared by the method for preparing the positive electrode material described in any of the above embodiments.
[0091] Based on this, an embodiment of the present application also provides a battery, including a positive electrode plate, the positive electrode plate includes a positive electrode material prepared by the preparation method of the positive electrode material described in any of the above embodiments or includes the positive electrode material described in any of the above embodiments.
[0092] It should be understood that since the positive electrode plate of the battery in the embodiment of the present application includes the positive electrode material prepared by the preparation method of the positive electrode material described in any of the above embodiments or includes the positive electrode material described in any of the above embodiments, the beneficial effects of the positive electrode material described in any of the above embodiments are applicable to the battery.
[0093] In some embodiments, the positive electrode sheet further comprises: a conductive agent, a binder and a dispersant, wherein the content of the positive electrode material may be 96wt% to 98wt%, the content of the conductive agent is 0 to 1wt%, the content of the binder is 1wt% to 4wt%, and the content of the dispersant is 0 to 1wt%. By controlling the ratio of the positive electrode material, the conductive agent, the binder and the dispersant, a positive electrode sheet with higher performance can be obtained.
[0094] Exemplarily, the conductive agent may include at least one of conductive carbon black, acetylene black, Ketjen black, and conductive graphite; the binder may include at least one of polyvinylidene fluoride, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyacrylates, and PAA polyacrylic acid; the dispersant may include at least one of N-methylpyrrolidone, polyvinylpyrrolidone, and polyvinyl alcohol.
[0095] In some embodiments, the compaction density of the positive electrode sheet can be 2.6 g / cm 3 ~2.9g / cm 3 Controlling the compaction density of the positive electrode sheet within the above range can improve the capacity performance and electrochemical performance of the positive electrode sheet.
[0096] In some embodiments, the positive electrode plate may include a positive electrode current collector and a positive electrode active material layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer may include a positive electrode material prepared by the preparation method of the positive electrode material described in any of the above embodiments or include the positive electrode material described in any of the above embodiments.
[0097] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two facing surfaces of the positive electrode current collector.
[0098] In some embodiments, the battery may be a secondary battery, and the secondary battery may be a lithium-ion secondary battery. Typically, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0099] The technical solution of the present application is further described below in combination with a plurality of embodiments and comparative examples.
[0100] The preparation of the positive electrode material in the embodiment and the comparative example includes the following steps:
[0101] S101: dispersing lithium carbonate, the first type of iron phosphate, the second type of iron phosphate, and a modifier (titanium dioxide, glucose, and polyethylene glycol) in an aqueous solution to obtain a mixed solution;
[0102] S102: sand-milling the mixed solution in step S101 to obtain a mixed sand-milled solution;
[0103] S103: drying the mixed sand-milled solution obtained in step S102 to obtain a mixed powder;
[0104] S104: The mixed powder obtained in step S103 is subjected to a first sintering and a second sintering in sequence and then crushed to obtain a positive electrode material including carbon-coated lithium iron phosphate and carbon-coated iron phosphide.
[0105] The specific experimental parameters of steps S101 to S104 in each embodiment and each comparative example are shown in Table 1 below.
[0106] Table 1
[0107]
[0108] The performance of the positive electrode materials obtained in the above embodiments and comparative examples was tested:
[0109] (1) Component analysis test of positive electrode materials
[0110] The positive electrode material is subjected to XRD test and energy spectrum analysis test.
[0111] Figure 2 The XRD diagrams of the positive electrode materials prepared in Example 2 and Comparative Example 1 are shown. In the diagram, θ in the horizontal axis is the incident angle of the X-ray, and the vertical axis is the diffraction intensity of the X-ray. Figure 3 for Figure 2 A local enlarged picture of Figure 3It can be seen that the diffraction peak of iron phosphide (Fe2P) appears in the XRD spectrum of the positive electrode material obtained in Example 2, and the diffraction peak of Fe2P does not appear in the XRD spectrum of the positive electrode material obtained in Comparative Example 1, which shows that the composition of the positive electrode material prepared in the present application includes iron phosphide, and the composition of the positive electrode material prepared in the comparative example does not include iron phosphide. In the present application, since the iron phosphate includes a first type of iron phosphate with a low iron-phosphorus ratio of 95% to 96.5%, the median particle size of the mixed sand-milled solution is controlled between 0.31 μm and 0.4 μm, so that the first type of iron phosphate generates iron phosphide after sand milling and heat treatment. In the comparative example, since the iron-phosphorus ratio of iron phosphate is relatively high, iron phosphide cannot be generated in the process of preparing the positive electrode material.
[0112] Figure 4 This is a scanning electron microscope image of the positive electrode material prepared in Example 2. In the scanning electron microscope observation, the brightness of the iron phosphide particles is higher than that of the lithium iron phosphate particles. Figure 4 The particles in the middle circle that are brighter than other areas are iron phosphide.
[0113] Figures 5 to 7 Corresponding to Figure 4 The energy spectrum of Fe, O and P elements in the middle area. Figures 5 to 7 The distribution of Fe, O and P elements in the corresponding Figure 4 In the area shown in the middle circle, the content of Fe is significantly higher than that of other areas, and the content of P is not significantly different from that of other areas. There is no O element in this area. Compared with lithium iron phosphate, the content of Fe in iron phosphide is higher and does not contain O element, and the content of P in the two is similar, which further shows that Figure 4 The particles shown in the middle circle are iron phosphide.
[0114] (2) Median particle size Dv50 test of positive electrode materials
[0115] First, take a clean beaker and add an appropriate amount of positive electrode material; then, add a surfactant and an appropriate amount of pure water into the beaker; next, perform ultrasonic treatment at a power of 120W for 5 minutes to ensure that the positive electrode material powder is completely dispersed in the water to obtain a mixed solution; then, pour the mixed solution into the injection tower of the laser particle size analyzer, and the positive electrode material particles circulate with the solution to the test optical path system. Under the irradiation of the laser beam, the particles receive and measure the energy distribution of the scattered light to obtain the particle size distribution characteristics of the particles (the shading degree in the test is 8% to 12%).
[0116] (3) Carbon content test in positive electrode materials
[0117] The carbon content test is carried out with reference to GB / T20123-2006. First, a certain amount of positive electrode material is weighed and placed in a crucible, and a solvent is added; then, the above experimental sample is burned; then, the gas generated after combustion is subjected to carbon analysis to obtain the carbon content.
[0118] (4) Resistivity test of positive electrode materials
[0119] Weigh an appropriate amount of cathode material powder sample and add the sample into the feeding chamber. Apply pressure at room temperature, where the pressure value is 8 MPa. Maintain the pressure for 10 seconds and then record the powder resistivity test result.
[0120] (5) Cathode material compaction density test
[0121] The compaction density test is carried out in accordance with GB / T24533-2009. A certain amount of cathode material powder is placed on a special compaction mold with a known diameter. A metal sheet is placed on the upper and lower parts of the mold, and the cathode material powder is placed in the middle. The corresponding powder thickness is tested while applying 3T pressure. The compaction density is calculated using the formula ρ=m / v, where ρ is the compaction density in g / cm 3 , m is the mass of the sample weighed, in g, and v is the volume of the sample after applying a pressure of 3T. The sample volume is obtained by multiplying the tested powder thickness by the area of the mold.
[0122] (6) Iron phosphide content test
[0123] First, prepare two clean plastic barrels with a volume of 10L and two magnetic bars with a diameter of 25mm, a length of 15cm, and a magnetic field strength of 12000GS. Take a heat shrink tube with a length of 18cm and a wall thickness of 250μm, and use a heat sealer to seal one end of the heat shrink tube. After confirming that the seal is completely watertight with water, put it on a magnetic bar, and then use a heat sealer to seal the other end of the heat shrink tube; then, add 6L of deionized water to the barrel, weigh 1.0±0.02kg (denoted as M1) of the positive electrode material powder sample and add it to the barrel, and put the prepared heat shrink tube with a magnetic bar into the barrel, cover the barrel, and place the barrel flat on a rolling machine and roll it at a constant speed for 35min at a speed of 100r / min; next, take out the magnetic bar. The heat shrink tube of the rod was removed from the clean beaker, and all the magnetic substances on the heat shrink tube were rinsed into the beaker with deionized water; next, 15 mL of deionized water was poured into the beaker for extracting the magnetic substances, and the beaker was ultrasonicated for 1 min. Then, a magnetic block was used to adsorb and aggregate the magnetic substances at the bottom of the beaker, and the solution in the beaker was poured into the waste liquid bucket. 10 mL of deionized water was added to the beaker, and the above steps were repeated 6 times. Finally, 10 mL of deionized water was added for suction filtration, and the inner wall of the beaker was rinsed to ensure that all the extracted magnetic substances were dispersed on the polyethersulfone filter membrane with a pore size of 12 μm. After suction filtration, the filter membrane with magnetic substances on the surface was placed in a 65°C oven and dried for 25 min; next, the filter membrane was placed in a 15 mL In a beaker containing N-methylpyrrolidone (NMP), ultrasonicate for 6 minutes to ensure that the filter membrane is completely dissolved, then use a magnetic block to adsorb and gather the magnetic material at the bottom of the beaker, pour the NMP in the beaker into a recovery bucket, and then use 3L of an aqueous solution with 4% methyl cellulose to rinse the magnetic material in the beaker into a clean plastic bucket, and add another prepared heat shrink tube with a magnetic rod, cover the bucket, and place the bucket flat on a rolling machine and roll it at a constant speed for 8 minutes at a speed of 120r / min; take out the heat shrink tube with a magnetic rod, remove the heat shrink tube in a clean beaker, and rinse all the magnetic material on the heat shrink tube into the beaker with deionized water. The test weight is the weight M2 of iron phosphide, and the iron phosphide content is (M2 / M1)*100%.
[0124] (7) Battery electrochemical performance test
[0125] The battery is prepared as follows:
[0126] The positive electrode materials prepared in the above-mentioned embodiments and comparative examples were uniformly mixed with polyvinylidene fluoride (PVDF) in NMP at a weight ratio of 98:2.0 to obtain positive electrode slurry, which was coated on aluminum foil, and then dried, cold pressed and cut to obtain positive electrode sheets.
[0127] The negative electrode active material artificial graphite, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) were mixed evenly in deionized water at a weight ratio of 96.5:0.7:1.8:1, and then coated on both sides of the copper foil, dried, and cold pressed to obtain the negative electrode sheet. The single-side coating amount was based on maintaining the negative electrode to positive electrode capacity ratio of 1.12.
[0128] A polyethylene (PE) porous polymer film was used as the isolation membrane.
[0129] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) were dissolved in 1M LiPF6 in a volume ratio of 1:1:1 and stirred evenly to obtain a 1 mol / L LiPF6 electrolyte.
[0130] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrodes to isolate them, and then wound to obtain a bare cell. The bare cell is placed in an outer package, and an electrolyte is added. The lithium-ion battery is then obtained through processes such as formation and standing.
[0131] (a) Full battery capacity test
[0132] At 25°C, the battery was discharged to 2.0V at a constant current of 0.33C, then charged to 3.65V at a constant current of 0.33C, then charged at a constant voltage of 3.65V until the current dropped to 0.05C, and then discharged to 2.0V at a constant current of 0.33C to obtain a 0.33C discharge capacity, and the 0.33C discharge capacity was divided by the weight of the positive electrode active material to obtain the 0.33C discharge gram capacity, recorded as the 0.33C gram capacity; the battery was charged to 3.65V at a constant current of 1C, and then charged at a constant voltage of 3.65V until the current dropped to 0.05C, and then discharged to 2.0V at a constant current of 2C to obtain a 2C discharge capacity, and the 2C discharge capacity was divided by the weight of the positive electrode active material to obtain the 2C discharge gram capacity, recorded as the 2C gram capacity.
[0133] (b) Full battery cycle performance test
[0134] At 45°C, the battery was charged to 3.65V at a constant current of 1C, then charged at a constant voltage of 3.65V until the current dropped to 0.05C, and then discharged to 2.0V at a constant current of 1C, and the discharge capacity of the first cycle (denoted as C1) was obtained; this charge and discharge were repeated until the 2000th cycle, and the discharge capacity after 2000 cycles (denoted as C2000) was obtained. The capacity retention rate after 2000 cycles at 45°C is: C2000 / C1.
[0135] The above test results are shown in Table 2.
[0136] It can be seen from the data of Example 1 to Example 13 in Table 2 that in this application, since the iron phosphate includes a first type of iron phosphate with a low iron-phosphorus ratio of 95% to 96.5%, the first type of iron phosphate generates iron phosphide after sanding and heat treatment. The generation of iron phosphide can prevent the formation of overly large primary particles from the fusion of small particles of lithium iron phosphate during the heat treatment process, thereby improving the compaction density and rate performance. On the other hand, the combination of ferromagnetic iron phosphide and antiferromagnetic lithium iron phosphate can produce a strong interface coupling effect between the two substances. This effect reduces the electron transfer resistance in the electrode, can significantly improve the kinetic properties of large lithium iron phosphate particles, and allow large particles to exert a higher gram capacity, thereby significantly improving the gram capacity, rate performance and cycle performance of lithium iron phosphate materials, and thus achieving a balance between the energy density and electrochemical performance of the positive electrode material.
[0137] It can be seen from the test results of Example 1 to Example 5 in Table 2 that as the content of the first type of iron phosphate increases, the iron phosphide content in the positive electrode material increases, and the resistivity of the positive electrode material powder gradually decreases, because iron phosphide has excellent conductivity. Due to the presence of iron phosphide, the resistivity of the positive electrode material can be significantly reduced. The test results of Example 1 to Example 5 show that as the iron phosphide content in the positive electrode material increases, the 0.33C gram capacity and the 2C gram capacity first increase and then decrease, and the capacity retention rate of 2000 cycles at 45°C gradually increases with the increase of the iron phosphide content. It can be seen that the gram capacity and cycle performance of the battery can be balanced by controlling the iron phosphide content in the positive electrode material, so that the overall performance of the battery can reach a better level.
[0138] It can be seen from the test results of Example 6 to Example 8 in Table 2 that as the iron-phosphorus ratio in the first type of iron phosphate increases, the iron phosphide content in the prepared positive electrode material decreases, that is, the lower the iron-phosphorus ratio in the first type of iron phosphate, the easier it is to generate iron phosphide. It can be seen from the test results of Example 2 and Example 9 that as the iron-phosphorus ratio in the second type of iron phosphate increases, the iron phosphide content in the prepared positive electrode material does not change much, and the 0.33C and 2C gram capacities of the battery are slightly improved. Therefore, controlling the mass ratio of the first type of iron phosphate to the second type of iron phosphate between (1:9) and (4:1) can make the carbon-coated iron phosphide and carbon-coated lithium iron phosphate in the prepared positive electrode material have a suitable proportion, thereby further improving the performance of the positive electrode material. In addition, in Example 7, since the iron-phosphorus ratio in the first type of iron phosphate is relatively low, the iron phosphide content in the prepared positive electrode material is relatively high, exceeding 2wt%. Although the battery's capacity retention rate after 2000 cycles at 45°C is relatively high, the 0.33C and 2C gram capacities are relatively low. Therefore, an iron phosphide content in the positive electrode material between 0.01wt% and 2wt% is a better solution for the present application.
[0139] It can be seen from the test results of Example 2, Example 10 and Example 11 in Table 2 that the smaller the value of the median particle size Dv50 of the mixed sand-milled solution, the higher the content of iron phosphide in the prepared positive electrode material, because the smaller the particle size of the mixed sand-milled solution, the larger the specific surface area of the first type of iron phosphate in the mixed sand-milled solution, which can promote the hydrolysis of the first type of iron phosphate during the sand-milling process, and then promote the formation of iron phosphide during the heat treatment process. Therefore, in this application, it is necessary to control the median particle size Dv50 of the mixed sand-milled solution between 0.31 μm and 0.4 μm to form iron phosphide during the heat treatment process, so as to finally obtain a higher quality positive electrode material.
[0140] It can be seen from the test results of Example 2, Example 12 and Example 13 in Table 2 that the higher the second sintering temperature, the higher the iron phosphide content in the obtained positive electrode material. Therefore, the sintering temperature of the second sintering between 750°C and 840°C can promote the formation of iron phosphide during the heat treatment process, thereby facilitating the final production of a higher quality positive electrode material.
[0141] Table 2
[0142]
[0143] Figure 8 The discharge curves of the batteries made of the positive electrode materials obtained in Example 2 and Comparative Example 1 at different rates. Figure 8 It can be seen that at 0.33C and 2C rates, the gram capacity of the battery made of the positive electrode material prepared in Example 2 is generally greater than the gram capacity of the battery made of the positive electrode material prepared in Comparative Example 1.
[0144] Fig. 9 The cycle performance test curves of the batteries made of the positive electrode materials obtained in Example 1 and Comparative Example 1 at 45°C are shown in FIG. Fig. 9 It can be seen that under the same number of cycles, the capacity retention rate of the battery made of the positive electrode material prepared in Example 1 is generally higher than the capacity retention rate of the battery made of the positive electrode material prepared in Comparative Example 1.
[0145] It can be seen from the test results of Comparative Examples 1 to 3 in Table 2 that in Comparative Examples 1 and 2, since the first type of iron phosphate is not included in the iron phosphate, iron phosphide is basically not generated when preparing the positive electrode material, especially in Comparative Example 2, since the iron-phosphorus ratio in the second type of iron phosphate is relatively high, iron phosphide is not generated when preparing the positive electrode material. It can be seen that the iron phosphate in the present application must contain a first type of iron phosphate with an iron-phosphorus ratio of 95% to 96.5%, and the median particle size Dv50 of the mixed sand-milling solution is controlled in a lower range of 0.31 μm to 0.4 μm, so that iron phosphide can be effectively generated when preparing the positive electrode material. In Comparative Example 3, since the iron phosphate mainly includes the first type of iron phosphate, the iron phosphide content in the prepared positive electrode material is relatively high, exceeding 2wt%. Although the battery's 45°C cycle 2000-week capacity retention rate is relatively high, the 0.33C and 2C gram capacities do not reach a better level.
[0146] It should be noted that the positive electrode material embodiments, positive electrode material preparation method embodiments, positive electrode plate embodiments and battery embodiments provided in the present application belong to the same concept; the technical features in the technical solutions recorded in each embodiment can be arbitrarily combined without conflict.
[0147] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations included in the claims. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.
Claims
1. A method for preparing a positive electrode material, characterized in that: The method comprises the following steps: S1: dispersing iron phosphate, a lithium source, and a modifier in an aqueous solution to obtain a mixed solution; the iron phosphate includes at least a first type of iron phosphate and a second type of iron phosphate, the first type of iron phosphate having an iron-to-phosphorus ratio of 95% to 96.5%, and the second type of iron phosphate having an iron-to-phosphorus ratio of 96.5% to 98%; the modifier includes a carbon source; S2: sand-milling the mixed solution to obtain a mixed sand-milled solution, wherein the median particle size Dv50 of the mixed sand-milled solution is 0.31 μm to 0.4 μm; S3: drying the mixed sand-milled solution to obtain a mixed powder; S4: pulverizing the mixed powder after heat treatment to obtain the positive electrode material including carbon-coated lithium iron phosphate and carbon-coated iron phosphide.
2. The method for preparing the positive electrode material according to claim 1, wherein: The mass ratio of the first type of iron phosphate to the second type of iron phosphate is (1:9) to (4:1).
3. The method for preparing the positive electrode material according to claim 1, wherein: The modifier further includes a dopant, and the dopant includes at least one of a Mg compound, a Ti compound, a V compound, a Zr compound, a Mn compound, a Nb compound, a Mo compound, and a B compound.
4. The method for preparing a positive electrode material according to any one of claims 1 to 3, characterized in that: The lithium source includes at least one of lithium carbonate, lithium nitrate, lithium hydroxide, and lithium acetate; and / or the carbon source includes at least one of sucrose, glucose, starch, polyethylene glycol, carbon black, carbon fiber tube, graphite, and graphene.
5. The method for preparing a positive electrode material according to any one of claims 1 to 3, characterized in that: The heat treatment includes sequentially performing a first sintering and a second sintering on the mixed powder.
6. The method for preparing the positive electrode material according to claim 5, wherein: The heat treatment satisfies at least one of the following characteristics (1) to (6): (1) The heating rate of the first sintering is 1°C / min to 10°C / min; (2) The sintering temperature of the first sintering is 200° C. to 350° C.; (3) The sintering time of the first sintering is 1 hour to 5 hours; (4) The heating rate of the second sintering is 1°C / min to 10°C / min; (5) The sintering temperature of the second sintering is 750°C to 840°C; (6) The sintering time of the second sintering is 6 hours to 15 hours.
7. A positive electrode material, characterized in that include: Carbon-coated lithium iron phosphate; Carbon-coated iron phosphide, the carbon-coated iron phosphide is distributed between the carbon-coated lithium iron phosphate particles; the content of the carbon-coated lithium iron phosphate is 98wt% to 99.99wt%, and the content of the carbon-coated iron phosphide is 0.01wt% to 2wt%.
8. The positive electrode material according to claim 7, characterized in that The positive electrode material satisfies at least one of the following characteristics (1) to (5): (1) The median particle size Dv50 of the positive electrode material is 0.7 μm to 2.5 μm; (2) The carbon content in the positive electrode material is 1.0 wt% to 1.6 wt%; (3) The resistivity of the positive electrode material is 1Ω·cm to 20Ω·cm; (4) The compaction density of the positive electrode material is 2.5 g / cm 3 ~2.8g / cm 3 ; (5) The particle size of the iron phosphide in the carbon-coated iron phosphide is 0.1 μm to 3 μm.
9. The positive electrode material according to claim 7 or 8, characterized in that The positive electrode material further comprises: The dopant includes at least one of a Mg compound, a Ti compound, a V compound, a Zr compound, a Mn compound, a Nb compound, a Mo compound, and a B compound.
10. A battery comprising a positive electrode plate, characterized in that: The positive electrode plate includes the positive electrode material prepared by the preparation method according to any one of claims 1 to 6 or includes the positive electrode material according to any one of claims 7 to 9.
Citation Information
Cited By
Positive electrode material and preparation method thereof, positive electrode plate, battery and energy storage device
CN120878817A
